Is world trade becoming more regionalised? - Peter J. Lloyd; Mia Mikic; Arun Jacob; Alexey Kravchenko; Pakkaporn Visetsilpanon; Franzisca Markschlaeger (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2018)
The proliferation of RTAs is a central feature of the world trade policy environment in the last 20 years. This paper provides an empirical study of the extent to which the formation of RTAs has changed the distribution of world goods trade among trading partners. To do this, it constructs a new measure, an index which measures the extent of bilateral trade between pairs of countries in each year. On average for the world economy this measure does not increase over the sample period 1981 to 2016. To study the impact of RTAs on the pattern of bilateralism in detail, we use a fixed effects regression model of countries for a panel dataset for countries in the Asia Pacific region. The evidence that the proliferation of RTAs has changed the country distribution of world of trade is very weak.
Keywords: F10; F14; 330; bilateralism; Index of bilateralism; RTAs; Asia Pacific region